2017
DOI: 10.1111/1744-7917.12484
|View full text |Cite
|
Sign up to set email alerts
|

Pupal emergence pattern in cactophilic Drosophila and the effect of host plants

Abstract: Drosophila buzzatii and D. koepferae are sibling cactophilic species. The former breeds primarily on prickly pears (genus Opuntia) whereas the latter breeds on columnar cacti of the genera Cereus and Trichocereus, although with certain degree of niche overlapping. We examined the interspecific differences in diurnal temporal patterns of adult emergence from puparia and evaluated whether this behavior is affected by rearing in the different cactus hosts available in nature. We detected important host-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…This variation could potentially depend on individual differences or on environmental factors that we could not control, such as the light/dark illumination cycle at the moment of adult emergence. Such circadian regulation of adult emergence has been observed in various Drosophila species (Ashburner et al, 2004;Mark et al, 2021;Powsner, 1935;Soto et al, 2018). However, the important variation in the last pupal stage is also found among individuals of the same cohort (Dataset S3 and S4).…”
Section: A Possible Temperature-buffering Mechanism During Pupal Deve...supporting
confidence: 62%
“…This variation could potentially depend on individual differences or on environmental factors that we could not control, such as the light/dark illumination cycle at the moment of adult emergence. Such circadian regulation of adult emergence has been observed in various Drosophila species (Ashburner et al, 2004;Mark et al, 2021;Powsner, 1935;Soto et al, 2018). However, the important variation in the last pupal stage is also found among individuals of the same cohort (Dataset S3 and S4).…”
Section: A Possible Temperature-buffering Mechanism During Pupal Deve...supporting
confidence: 62%
“…This variation could potentially depend on individual differences or on environmental factors that we could not control, such as the light/dark illumination cycle at the moment of adult emergence. Such circadian regulation of adult emergence has been observed in various Drosophila species (Ashburner et al, 2004; Mark et al, 2021; Powsner, 1935; Soto et al, 2018). However, the important variation in the last pupal stage is also found among individuals of the same cohort (Datasets S1 and S2).…”
Section: Discussionmentioning
confidence: 73%
“…However, correlation analyses recently performed between both traits in D. buzzatii and D. koepferae showed an association that may change with the environment. In particular, the association between traits did not vary with the rearing medium in D. buzzatii , although it was significant in D. koepferae only when flies were raised in Opuntia sulphurea G Don ex Salm‐Dyck (i.e., it was not significant when they were raised in T. terscheckii ; Soto et al, 2018). Even though the number of replicates in this study is insufficient to perform reliable correlation analyses, we also observed that viability and DT changed jointly in D. buzzatii when the P450 enzymatic activity was inhibited with PBO, whereas they changed more independently in D. koepferae .…”
Section: Discussionmentioning
confidence: 98%